2022
DOI: 10.3168/jds.2021-21752
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of subclinical endometritis in Norwegian Red cows

Abstract: Subclinical endometritis (SCE) is highly prevalent in dairy cows, causing negative effects on reproductive outcomes and the producer economy. Genetic selection for animals with better resilience against uterine disease should be prioritized due to both sustainability and animal welfare. Therefore, the aim of the present study was to estimate the heritability of SCE in the Norwegian Red (NR) population. Moreover, future perspectives of the condition as a fertility phenotype for breeding are discussed. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Numerous researchers argue that in addition to the clinical manifestations of diseases of the reproductive organs, cows are diagnosed with a subclinical or latent form of endometritis, which is associated with the widespread use of hormonal stimulation of oestrus and artificial insemination. They account for up to 75-80.0 % of nonspecific inflammation of the uterus (LeBlanc et al, 2011;Diaz-Lundahl et al, 2022;Pascottini et al, 2023).…”
Section: Postpartum Pathology Of the Uterusmentioning
confidence: 99%
“…Numerous researchers argue that in addition to the clinical manifestations of diseases of the reproductive organs, cows are diagnosed with a subclinical or latent form of endometritis, which is associated with the widespread use of hormonal stimulation of oestrus and artificial insemination. They account for up to 75-80.0 % of nonspecific inflammation of the uterus (LeBlanc et al, 2011;Diaz-Lundahl et al, 2022;Pascottini et al, 2023).…”
Section: Postpartum Pathology Of the Uterusmentioning
confidence: 99%
“…Recently, we found that NR had a high prevalence of SCE at AI with only a moderate effect on fertility compared to Holstein [26]. One study showed an indication of this condition having a heritable component in NR [27], but the majority of the variation was not explained by this factor. Hence, it is not known if the relatively positive outcome from SCE in NR is due to a beneficial immune regulation, certain traits of the microbiota, other factors, or combinations of such.…”
Section: Introductionmentioning
confidence: 97%